What kind of support do we need when favouring smes in public procurement – Hungarian case - Tátrai, Tünde (Piccola Impresa / Small Business, 2013)
The aim of this article is to point out that it is not enough to create a general and unified SME-friendly public procurement policy at European level and to highlight the importance of taking the regional and national characteristics of public procurement markets into consideration. The European SME-friendly public procurement policy is not viable in the sense that it is not about genuinely small enterprises. National legislation, however, frequently mistakes SME-friendly rules for supporting local enterprises, which distorts the original set of objectives. Going beyond giving preference to SMEs and increasing the employment rate through public procurement within the set of objectives of an SME-friendly system may mean progress. The SMEs’ role in job creation and their contribution to innovation need to be better characterized. The lack of a deep understanding of the connections between SMEs and the consequences of their increasingly important role call for remedy. For the time being, Member States provide no more than symptomatic treatment and superficial solutions at European level. Member States, especially the new ones are in need of real decision making support, not merely practical advice for their Contracting Authorities. The Hungarian and the Romanian examples provide evidence that it is necessary to rethink the policy in spite of the achievements related to the role of SMEs in public procurement